Peran Orangtua dalam Menfasilitasi Tumbuh Kembang Anak Usia Dini Di Dusun Kaccope Desa Bulu-Bulu Kecamatan Tonra Kab.Bone - Febriansa, Febriansa; Muhammad Nur Alamsyah, Muhammad Nur Alamsyah (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
ABSTRACTThis research aims to analyze the role of parents in facilitating the growth and development of early childhood in Kaccope Hamlet, Bulu-Bulu Village, Tonra District, Bone Regency. The research focus includes the role of parents as facilitators, motivators, and mentors, as well as how these roles can be improved to support children's development more optimally. This research used a descriptive quantitative approach, with a population of 45 parents who had children aged 4-6 years. Data collection techniques were carried out through questionnaires with a Likert scale and documentation of children's daily activities. Data were analyzed using descriptive statistics to determine the level of implementation of parental roles in three main aspects. The research results show that the role of parents has generally been implemented well, with success rates for each aspect as follows: facilitator (87.9%), motivator (95.6%), and guide (92.9%). However, there are still weaknesses in providing conducive learning facilities and the ability to guide children to make independent decisions. Therefore, a parenting education program is needed to increase the capacity of parents to support the growth and development of early childhood.Keywords: role of parents, early childhood education, facilitator, motivator, guide